Menyingkap Social Nature Industri Musik Digital Dalam Negeri - Awang Dharmawan (IKOM UMY, 2015)
The bockground of this paper is based on survey results of nongovernmentaL orgonbation HeaL Our Music, a day in Indonesia thot there are 7,920,944 iLlegol downLoading of digitol music. lt means the same amount every second there are 92 iLlegol music downLoods. Thus the authors mapped the three-point discussion thot is the reaLity of piracy in the country, supporting the creative industries of music copyright, and literacy for music lovers. The concLusion of this paper is the existence of copyright low ore still lacking, the government should provide technical systems thot legal music downloads and cheap woy for music lovers.